2022
DOI: 10.1038/s41598-022-09436-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic diversity of fecal Candida albicans strains in irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a common disorder characterized by chronic abdominal pain and changes in bowel movements. Visceral hypersensitivity is thought to be responsible for pain complaints in a subset of patients. In an IBS-like animal model, visceral hypersensitivity was triggered by intestinal fungi, and lower mycobiota α-diversity in IBS patients was accompanied by a shift toward increased presence of Candida albicans and Saccharomyces cerevisiae. Yet, this shift was observed in hypersensitive as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…While this was not shown to be explicitly NLRP3 dependent, it is reasonable to speculate given that one study has demonstrated hyperactivation of NLRP3 in Crohn’s Disease patients (60%) as compared to healthy controls (28.6%) ( 64 ). Similar to vaginal isolates, GI isolates exhibit phenotypic heterogeneity with respect to growth, yeast-to-hypha transition, and ECE1 expression, underscoring that isolate-to-isolate diversity impacts disease outcome ( 65 ). Therefore, CL may push or exacerbate GI dysbiosis and precipitate immunopathogenesis of the human gut.…”
Section: Directly Influences Mucosal and Systemic Pathologiesmentioning
confidence: 99%
“…While this was not shown to be explicitly NLRP3 dependent, it is reasonable to speculate given that one study has demonstrated hyperactivation of NLRP3 in Crohn’s Disease patients (60%) as compared to healthy controls (28.6%) ( 64 ). Similar to vaginal isolates, GI isolates exhibit phenotypic heterogeneity with respect to growth, yeast-to-hypha transition, and ECE1 expression, underscoring that isolate-to-isolate diversity impacts disease outcome ( 65 ). Therefore, CL may push or exacerbate GI dysbiosis and precipitate immunopathogenesis of the human gut.…”
Section: Directly Influences Mucosal and Systemic Pathologiesmentioning
confidence: 99%
“…Similar to the lack of taxonomic classification or identification, differences between fungal strains within individuals cannot be detected using ITS metabarcoding nor by Sanger sequencing. This sub-species variability may be important in disease as previously described for IBD and IBS [ 22 , 24 , 28 ]. More specialized techniques such as Amplified Fragment Length Polymorphism fingerprinting (AFLP), Random Amplified Polymorphic DNA (RAPD), microsatellite typing or whole genome sequencing (WGS) are needed to properly describe these variations.…”
Section: Challenges and Recommendations Regarding Studies Of Intestin...mentioning
confidence: 82%
“…Phenotypic characteristics including adherence to epithelial cells, enzyme release, and gene expression alterations during yeast-to-hyphae transition ( ECE1, ALS3 , and SAP2 ) were observed between the strains. No clear-cut association was observed between virulence-associated traits and visceral sensitivity status, in part due to small group sized in this study [ 24 ]. Further research should indicate whether the virulent capacity of C. albicans strains indeed contribute to altered sensitivity status and abdominal pain in IBS.…”
Section: The Role Of Candida Spp In Intestinal Dis...mentioning
confidence: 96%
See 1 more Smart Citation
“…For example, S. cerevisiae and C. albicans isolated from the feces of patients with CD displayed different in vitro and in vivo immune responses 68 . Moreover, C. albicans strains isolated from patients with irritable bowel syndrome (IBS) displayed phenotypic diversities, and genotypic analysis revealed that the strains isolated from the gut of hypersensitive IBS patients partially clustered together 69 . However, whether the colonization of a specific body site is associated with genotypic and phenotypic diversities, including virulence, remains unclear.…”
Section: Discussionmentioning
confidence: 99%